Design and Implementation Results of an Integrated System for Converting Fruit Waste into Bio-Energy Briquettes: Focus on the Pyrolyzer, Disc Mill, Cylindrical Oven, and Hydraulic Press Machine - M. Alkadri Perdana; Johny Custer; Andri Nofiar.Am; Lukman Hakim Nasution; Wahyu Triyono; Siti Rahayu (Information Technology and Science (ITScience), 2025)
Fruit waste poses significant environmental and socioeconomic challenges, particularly in agricultural countries such as Indonesia. This study presents the development of an integrated system to convert fruit biomass waste into bio-energy briquettes using a pyrolyzer, disc mill, cylindrical oven, and hydraulic press. Pyrolysis was conducted at 350–500°C under limited oxygen, producing solid carbon, bio-oil, and syngas. The carbonized material was then milled, sieved, dried, and compacted into high-density briquettes. Laboratory characterization using X-Ray Fluorescence (XRF), Field Emission Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (FESEM-EDS), and bomb calorimetry revealed a carbon content of approximately 82.5% and an average calorific value of 5,800 kcal/kg with a moisture content of 9.4%, indicating high energy potential and good mechanical stability. The system achieved a production capacity of 300–500 kg/day, making it suitable for small-scale, community-based renewable energy applications. The results confirm the technical feasibility and economic viability of the integrated system while supporting rural energy independence and local economic development. Future work should focus on system automation and exploring diverse biomass feedstocks for broader implementation.